2012
DOI: 10.1063/1.3676613
|View full text |Cite
|
Sign up to set email alerts
|

Co-ferrite spinel and FeCo alloy core shell nanocomposites and mesoporous systems for multifunctional applications

Abstract: We report on the fabrication of condensed and mesoporous silica coated CoFe2O4 and FeCo alloy magnetic nanocomposites. The CoFe2O4 magnetic nanoparticles were encapsulated by well defined silica layer with a uniform thickness of 5 nm. The mesoporous silica shells lead to a larger magnetic coercivity than that of the pure CoFe2O4 magnetic nanoparticles due to decrease of interparticle interactions and magneto-elastic anisotropy. In addition, the FeCo nanoparticles were coated with condensed and mesoporous silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…With only a few exceptions (e.g., Zn 0.4 Fe 2.6 O 4 MNPs), alloyed MNPs such as FeCo generally exhibit higher Ms values (e.g., 150–200 emu/g) [102,103]. The enhancement has been attributed to the absence of the non-ferromagnetic “oxygen” component found in many of the alternative mixed-metal structures.…”
Section: Effect Of Different Parameters On Magnetic Propertiesmentioning
confidence: 99%
“…With only a few exceptions (e.g., Zn 0.4 Fe 2.6 O 4 MNPs), alloyed MNPs such as FeCo generally exhibit higher Ms values (e.g., 150–200 emu/g) [102,103]. The enhancement has been attributed to the absence of the non-ferromagnetic “oxygen” component found in many of the alternative mixed-metal structures.…”
Section: Effect Of Different Parameters On Magnetic Propertiesmentioning
confidence: 99%
“…FeCo MNPs usually exhibit high Ms values (122–230 emu/g) compared with Co MNPs (Chaubey et al 2007 ), due to the absence of the non-magnetic oxygen component (Zhang et al 2012 ). However, the ease of oxidation in the presence of air is the key issue for these alloys (Zhang et al 2012 ).…”
Section: Biomaterials For Magnetic Hyperthermiamentioning
confidence: 99%
“…The higher saturation magnetization reported in this study is attributed to the perfectly ordered single-domains magnetic NPs [3]. On the other hand, the lower coercivity is found due to the decrease of interparticle interactions and magneto-elastic anisotropy [22]. The retentivity of the magnetic nanomaterials is equal to M r = 13.5 emug − 1 as shown in Fig.…”
Section: Magnetic Propertiesmentioning
confidence: 52%
“…The NPs behaves as a soft ferrimagnet with coercivity, H c = 620 Oe and saturation magnetization, M s = 60 emug − 1 at room temperature. It is observed that the saturation magnetization of CoFe 2 O 4 is higher than the values obtained by modified wet chemical process and hydrothermal process [22,23]. The higher saturation magnetization reported in this study is attributed to the perfectly ordered single-domains magnetic NPs [3].…”
Section: Magnetic Propertiesmentioning
confidence: 63%